Impact of the 2014 International Society of Urological Pathology Grading System on Concept of High-Risk Prostate Cancer: Comparison of Long-Term Oncological Outcomes in Patients Undergoing Radical Prostatectomy - Milonas, Daimantas; Venclovas, Žilvinas; Gudinaviciene, Inga; Auskalnis, Stasys; Zviniene, Kristina; Jurkiene, Nemira; Basevicius, Algidas; Patasius, Ausvydas; Jievaltas, Mindaugas; Joniau, Steven (Frontiers in Oncology, 2019)
Objective: To investigate the relationship between the new International Society of Urological Pathology (ISUP) grading system, biochemical recurrence (BCR), clinical progression (CP) and cancer related death (CRD) after open radical prostatectomy (RP) and determine whether the 2014 ISUP grading system influences the concept of high-risk prostate cancer (HRPCa). Patients and Methods: A total of 1,754 men who underwent RP from 2005 to 2017 were identified from a database at a single tertiary institution. Histopathology reports were reassessed according to the 2014 ISUP grading system. All preoperative, pathological, and clinical follow-up data were obtained. Univariable and multivariable Cox regression, Kaplan-Meier and log-rank analyses were performed. Results: At a median (quartiles) follow-up of 83 (48–123) months, 446 men (25.4%) had BCR, 77 (4.4%) had CP and 39 (2.2%) died from cancer. Grade groups 1, 2, 3, 4, and 5 were detected in 404 (23%), 931 (53.1%), 200 (11.4%), 93 (5.3%), and 126 (7.2%), respectively. 10-year biochemical progression free survival difference between Grade group 3 and 4 was minor but significant (log-rank p = 0.045). There was no difference between Grade groups 3 and 4 comparing 10-year clinical progression free and 10-year cancer specific survival: p = 0.82 and p = 0.39, respectively. Group 5 had the worst survival rates in comparison with other groups (from p < 0.005 to p < 0.0001) in all survival analyses. Pathological stage (hazard ratio (HR) 2.6, p < 0.001), positive surgical margins (HR 2.2, p < 0.0001) and Grade group (HR 10.4, p < 0.0001) were independent predictors for BCR. Stage and Grade group were detected as independent predictors for CP–HR 6.0, p < 0.0001 and HR 35.6, p < 0.0001, respectively. Only Grade group 5 (HR 12.9, p = 0.001) and pT3b (HR 5.9, p = 0.001) independently predicted CRD. Conclusions: The new ISUP 2014 grading system is the most significant independent predictor for BCR, CP, and CRD. Grade group 3 and 4 had similar long-term disease progression survival rates and could potentially be stratified in the same risk group. High-risk cancer associated only with group 5.